DEVELOPMENT OF UKRAINIAN AIR TRAFFIC IN THE EUROPEAN INTEGRATION CONDITIONS - Вишновецький, Вадим Михайлович; Стрілько, Андрій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to study the development of Ukraine’s air traffic in accordance with European Union standards. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: generalized mechanisms for improving the development and coordination of air traffic in accordance with international standards. Discussion: clarification of the normative fixing of air traffic in domestic legislation, the role of Ukrainian aviation providers and airline operators in the «free sky» of Europe, the state of implementation of international standards and participation of Ukraine in international organizations. Transport, as an infrastructure industry, must be ahead of the pace in order to promote the country’s rapid economic and social development. The Ukrainian aviation transport system is on the path of integration with the European aviation transport system. The implementation of the task of gradual integration into European and world transport systems involves the implementation of European norms and standards in the air transport sphere, adherence to key international conventions and agreements, development of aviation infrastructure, international transport corridors and checkpoints, security and environmental friendliness. Ukraine’s intention to cooperate with the EU in order to improve the functioning of the trans-European transport networks is based on the relevant plan of the European Commission to extend the major trans-European transport axes to the territory of Ukraine. New agreements in this direction allow Ukraine to integrate into the Single European Aviation Market, but to achieve this goal it is necessary to harmonize the Ukrainian air transport network in accordance with European standards on the basis of not declarative but real implementation of state target programs in accordance with the system of international treaties. The aviation network to a single EU aviation network. Recommendations on the strategy and mechanisms of integration of Ukraine’s aviation network into a single EU transport system have been developed.